Enhancing EFL Speaking Proficiency Through Point of View Lesson Technique: A Classroom Action Research Study - Hamdi, Asrul; Asrobi, Maman (Sumber Belajar Sejahtera, 2025)
This study aimed to investigate the effectiveness of the Point of View Lesson technique in improving the speaking ability of first-semester students in an English education program. The research was conducted using a classroom action research (CAR) design over two cycles, each consisting of planning, acting, observing, and reflecting stages. A total of 40 students participated in the intervention, which focused on helping them retell stories and personal experiences from different narrative perspectives to enhance fluency, vocabulary use, and grammatical accuracy. Data were collected through pre-tests and post-tests, classroom observations, and reflective journals. The results showed a significant improvement in students' speaking performance, with the mean score increasing from 8.25 in the pre-test to 9.50 in the post-test. Observational data also indicated greater student engagement, confidence, and ability to shift narrative perspectives when speaking. These findings suggest that the Point of View Lesson technique can be a practical pedagogical approach for developing speaking skills in EFL learners, particularly when integrated with reflective teaching practices in real classroom contexts.